(untitled) (Proceedings of the International Conference on Education, 2023)
Children with disabilities are among the most marginalized and at risk of losing out on quality learning opportunities. Even prior to the Covid-19 pandemic, many education systems remained inequitable and either excluded children with the most complex disabilities or lacked quality in implementation. The Perkins Quality Indicators (PQIs) provide a metric to measure and assess programs that serve children with complex disabilities by identifying current good practices and areas for improvement. Program staff may use the PQIs for self-reflection, evaluation and planning. The tool may also be used by program administrators and external evaluators, in collaboration with program staff. The PQIs address 9 program areas: building community/ inclusive culture, program planning and classroom organization, learning environment and materials, communication and social relationships, assessment and progress monitoring, curriculum and instruction, family support, administration and support, and governmental collaborations. We aim to present the PQIs as a practical tool that can be used to support and document growth of quality programs over time through the development of priorities for both teacher professional development and school-based development, at individual, local, district, division, regional, and national levels. The PQIs have been implemented in at least 17 countries across 4 continents, including in the Philippines; we will present a representative case study of implementation in the Philippines to demonstrate how the PQIs help to create a roadmap for programs to achieve excellence and accelerate progress. We conclude that the implementation of the PQIs in settings that serve children and youth with complex disabilities has great potential for making measurable improvements in the quality of these programs, accelerating progress toward the global goals of more equitable education, especially after learning setbacks caused by the Covid-19 pandemic.